2020
DOI: 10.18280/rcma.303-409
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis the Impact of Unsymmetrical Bending on Aluminum Honeycomb Sandwich Beams with Polyester Resin/Glass Fibers Using Finite Element Method

Abstract: Sandwich structures are low-weight and have the best stiffness and a relatively high flexural strength, what makes using them continues to increase rapidly for industrial applications ranging from aeronautics, road vehicles, satellites, ships and civil engineering to mention only a few. The paper presents investigation and analysis of the behavior of composite sandwich beams with polyester resin/glass fibers skins (T800/M300) and aluminum honeycomb core under unsymmetrical bending impact. In this work we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Therefore, many efforts have been made to develop new designs, such as composite tubes that combine thin-walled metal tubes with other parts, which show many favorable properties [1]. The investigated components include lattice [2][3][4][5], foam [6][7][8][9], honeycomb [10][11][12][13], fold [14], ortho-grid [15,16], circumferential [17], and longitudinal corrugated [18,19] cores. It was demonstrated that the dual-bearing capacity of tube and foam improve the overall stability and mechanical performance of the combined structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have been made to develop new designs, such as composite tubes that combine thin-walled metal tubes with other parts, which show many favorable properties [1]. The investigated components include lattice [2][3][4][5], foam [6][7][8][9], honeycomb [10][11][12][13], fold [14], ortho-grid [15,16], circumferential [17], and longitudinal corrugated [18,19] cores. It was demonstrated that the dual-bearing capacity of tube and foam improve the overall stability and mechanical performance of the combined structure [20].…”
Section: Introductionmentioning
confidence: 99%